Maximização da cobertura redundante em redes de sensores visuais sem fio para monitoramento de alvos - Silva, Tassalon Ferreira da (2015)
This work have proposed the adaptation and the development of algorithms for maximization of the redundant coverage of targets in wireless visual sensor networks. The most relevant concepts were described about the theory of visual sensors networks, development techniques of coverage algorithms and the details of the performed implementations. Besides, tests and comparisons were performed in simulation environments to demonstrate the obtained results, as well as to evaluate the performance of each developed algorithm of redundant coverage.